2017
DOI: 10.1001/jamaneurol.2017.1317
|View full text |Cite
|
Sign up to set email alerts
|

Association of Playing High School Football With Cognition and Mental Health Later in Life

Abstract: IMPORTANCE American football is the largest participation sport in US high schools and is a leading cause of concussion among adolescents. Little is known about the long-term cognitive and mental health consequences of exposure to football-related head trauma at the high school level.OBJECTIVE To estimate the association of playing high school football with cognitive impairment and depression at 65 years of age. DESIGN, SETTING, AND PARTICIPANTSA representative sample of male high school students who graduated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
94
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 58 publications
3
94
0
Order By: Relevance
“…Several studies have reported that NFL and college football athletes with a history of concussion are more likely to experience depression, although the risk of mental health issues, including suicide, among former NFL players is lower than age-matched controls 101–103. Former high school football players show no difference in cognitive function testing and have lower depression scores when compared with non-contact sport controls 104. Mental health issues are common, multifactorial and often present independent of participation in contact or collision sport.…”
Section: Risks Related To Concussionmentioning
confidence: 92%
“…Several studies have reported that NFL and college football athletes with a history of concussion are more likely to experience depression, although the risk of mental health issues, including suicide, among former NFL players is lower than age-matched controls 101–103. Former high school football players show no difference in cognitive function testing and have lower depression scores when compared with non-contact sport controls 104. Mental health issues are common, multifactorial and often present independent of participation in contact or collision sport.…”
Section: Risks Related To Concussionmentioning
confidence: 92%
“…Brain injury, of any severity, in the developing brain is complicated by ongoing cerebral maturation. 26 Of crucial importance in prognosis is the rapid increase in reactive stressors that heighten the metabolic demand on the brain. 27 Concussion induces inflammatory sensory stimulus that is preferentially transmitted to brainstem and specific hypothalamic nuclei which have direct connection to the hypothalamic paraventricular nucleus.…”
Section: Casazza K Et Al: Nutrition In Sports-related Concussionmentioning
confidence: 99%
“…However, the results of the study by Deshpande et al 9 offer some reassurance against CTE being a widespread epidemic among former football players, at least when considering high school football players as a group and examining long-term outcomes among this group on average.…”
mentioning
confidence: 99%
“…Additional strengths of the study by Deshpande et al 9 include their careful consideration of some potential confounding factors, comparison of football players with different control groups, and analysis examining potential attrition bias. Future longitudinal, population-based studies should continue to use such thoughtfulness in data analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation